Low-dimensional coal-based hard carbon material with high sodium storage capacity and high initial coulombic efficiency and preparation method of low-dimensional coal-based hard carbon material
Through technical means such as liquid phase oxidation method and graphite crystal template assisted calcination, low-dimensional coal-based hard carbon materials with high sodium storage capacity and high initial Coulomb efficiency were prepared, which solved the problem of difficulty in taking into account high sodium storage capacity and high initial Coulomb efficiency in the existing technology, and achieved high performance and low cost preparation of sodium ion battery negative electrode materials.
Patent Information
- Application Number
- CN202411800460.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The application of existing coal-based hard carbon materials in sodium ion batteries faces the problem of difficult to take into account both high sodium storage capacity and high initial Coulomb efficiency.
The coal-oxide nanosheets and coal-oxide-based graphene quantum dots were prepared by liquid phase oxidation. The amine-containing compounds were crosslinked and self-assembled, combined with graphite crystal template assisted calcination, the microstructure of coal-based hard carbon materials was regulated, and low-dimensional coal-based hard carbon materials with high sodium storage capacity and high initial Coulomb efficiency were prepared.
The specific capacity of sodium storage at 0.02A g-1 current density is achieved to reach 420.40mA h g-1, and at the same time, it has a high initial Coulomb efficiency of 91.97%, which reduces the preparation cost, simplifies the process, and improves the electrochemical performance.
Smart Images

Figure CN119612493A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode materials for alkali metal ion batteries, and specifically relates to a low-dimensional coal-based hard carbon material having both high sodium storage capacity and high initial coulombic efficiency and a preparation method thereof. Background Art
[0002] At present, most energy storage systems with high energy density and long cycle life use lithium-ion battery technology. However, with the consumption of lithium resources and the gradual increase in costs, it is crucial to develop new electrochemical energy storage devices. Since sodium resources are abundant and the chemical composition is compatible with mature lithium-ion battery technology, sodium-ion batteries have attracted much attention as a viable alternative to lithium-ion batteries. However, the graphite-like negative electrode materials that promote the commercialization of lithium-ion batteries have poor sodium ion storage capacity, making their application in sodium-ion batteries face great challenges. In 2000, Stevens and Dahn discovered that hard carbon has a storage capacity of 300mAh g -1 The existing precursors for producing hard carbon include biomass, resin, high molecular polymer, etc.; these precursors are usually high in cost and low in carbon yield, which greatly increases the overall manufacturing cost of sodium-ion batteries. Based on this, it is very important to develop low-cost and high-performance hard carbon negative electrode materials for sodium-ion batteries.
[0003] As a high-quality, cheap and readily available fuel and an important chemical raw material, coal is widely used in the fields of energy, chemical industry and materials. In terms of chemical composition, coal has an extremely high carbon content and is a natural precursor of carbon materials. In terms of molecular structure, coal has the characteristics of a macromolecular polymer, which can be considered as a rigid network structure formed by multiple basic structural units with similar structures connected by bridge bonds in three-dimensional space. The degree of cross-linking is high and the basic structural units are not easy to form parallel arrangements. In addition, there are a large number of oxygen-containing functional groups and side chain structures in coal, which will prevent the orderly rearrangement of graphite-like microcrystalline structures during pyrolysis and carbonization. After dehydrogenation, condensation, hydrogen transfer and isomerization at high temperature, coal will form a highly twisted structure with curved graphitized carbon layers stacked on each other and amorphous carbon connected, rich nanopores and large interlayer spacing. In recent years, researchers have conducted a lot of research on the microstructure regulation and electrochemical sodium storage mechanism of coal-based hard carbon materials, confirming that the graphite microcrystalline structure and defect sites are the key influencing factors determining its sodium storage performance.
[0004] At present, researchers mainly regulate the microstructure of coal-based hard carbon materials through strategies such as high-temperature carbonization (X.Ou, D.Gong, C.Han, Z.Liu, Y.Tang, Adv.Mater., 2021, 11, 2102498), precursor pre-oxidation (H.Chen, N.Sun, Q.Zhu, et al., Adv.Sci., 2022, 9, 2200023) and heteroatom doping (J.Wan, S.Fan, J.Qu, et al., ACS Energy Lett., 2024, 9, 627-635.). However, the above methods all have several problems: (1) Increasing the pyrolysis temperature will increase the short-range order of pseudo-graphite domains while reducing the interlayer spacing, thereby seriously reducing the reversible capacity and the diffusion kinetics of metal ions; (2) Changing the pre-oxidation degree of the precursor can adjust the graphite microstructure of coal-based hard carbon, but it is difficult to reverse the disorder of pseudo-graphite domains; (3) Heteroatom doping defects can change the electronic distribution of the carbon skeleton and improve chemical inertness, but its strong binding energy with sodium ions and the occurrence of side reactions make the initial Coulomb efficiency (ICE) of coal-based hard carbon negative electrode materials low. In recent years, the graphite crystal template induction method is believed to be able to induce partial lattice reconstruction of biomass-based hard carbon and promote the formation of graphite-like crystals, thereby improving its sodium storage capacity and ICE as the negative electrode of sodium ion batteries (X. Li, J. Sun, W. Zhao, et al., Adv. Funt. Mater., 2022, 32, 2106980). Unlike biomass precursors, the rigid cross-linked network structure of coal itself limits the flexible "top-down" regulation of the coal-based hard carbon microstructure by the graphite crystal template induction method, which in turn makes it difficult to take into account both the reversible sodium storage capacity and ICE of coal-based hard carbon materials as the negative electrode of sodium ion batteries. Summary of the invention
[0005] In order to solve the problem of the contradictory competitive relationship between the graphite microcrystalline structure and defect sites of the existing coal-based hard carbon materials, the present invention provides a method for preparing a low-dimensional coal-based hard carbon material with both high sodium storage capacity and high initial coulomb efficiency. The Xinjiang bituminous coal is oxidized and depolymerized by liquid phase oxidation to obtain active components such as oxidized coal nanosheets (OC) and oxidized coal-based graphene quantum dots (GQDs). Secondly, the above-mentioned active components are cross-linked, self-assembled and deoxygenated and reduced by amine-containing compounds, so as to prepare a low-dimensional coal-based precursor with a simple molecular structure and easy to adjust "bottom-up". Finally, a graphite crystal template is used to assist in the calcination of the coal-based precursor, and the carbon atom migration, atomic fragment rearrangement and lattice reconstruction during coal pyrolysis are regulated, and then the crystal quality is improved by high-temperature calcination, thereby preparing a low-dimensional coal-based hard carbon negative electrode material with both high sodium storage capacity and high ICE. Another technical problem to be solved by the present invention is to provide a low-dimensional coal-based hard carbon material with both high sodium storage capacity and high initial coulombic efficiency. The low-dimensional coal-based hard carbon material is used as the negative electrode of a sodium ion battery. -1 The specific capacity of sodium storage can reach 420.40 mA hg -1 , while also having a high ICE of 91.97%.
[0006] Technical solution: In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a low-dimensional coal-based hard carbon material with both high sodium storage capacity and high initial coulombic efficiency, comprising: oxidizing and depolymerizing Xinjiang bituminous coal by a liquid phase oxidation method to obtain oxidized coal nanosheets and oxidized coal-based graphene quantum dots; cross-linking, self-assembling and deoxidation-reducing a mixture of oxidized coal nanosheets and oxidized coal-based graphene quantum dots or oxidized coal nanosheets by an amine compound to obtain a low-dimensional coal-based precursor; using a graphite plate to assist in calcining the coal-based precursor, and then calcining at a high temperature to prepare a low-dimensional coal-based hard carbon material with both high sodium storage capacity and high ICE.
[0008] The method for preparing a low-dimensional coal-based hard carbon material with both high sodium storage capacity and high initial coulombic efficiency comprises: using a nitric acid / sulfuric acid oxidation system to oxidatively depolymerize Xinjiang bituminous coal for 3 to 6 hours, wherein the mass volume ratio of coal powder to the oxidation system is 1 g:24 mL; and the volume ratio of sulfuric acid to nitric acid is 1:1 to 3:1; preferably, using a nitric acid / sulfuric acid oxidation system to oxidatively depolymerize Xinjiang bituminous coal for 5 hours, wherein the volume ratio of sulfuric acid to nitric acid is 3:1.
[0009] The method for preparing a low-dimensional coal-based hard carbon material having both high sodium storage capacity and high initial coulombic efficiency, wherein the amine-containing compound is any one of ethylenediamine, octanediamine, o- / m- / p-phenylenediamine, diethylenetriamine, triethylenetetramine, polyetheramine, polyimide, piperazine or urea.
[0010] The preparation method of the low-dimensional coal-based hard carbon material with high sodium storage capacity and high initial coulombic efficiency comprises the following steps: adding an amine-containing compound and then hydroheating the material at 80 to 120°C for 4 to 8 hours; the mass volume of the oxidized coal nanosheets and the amine-containing compound is 3g:1 to 8mL, and the mass ratio of the oxidized coal nanosheets to the oxidized coal-based graphene quantum dots is 3:1 to 100:1; preferably, the amine-containing compound is added and then hydroheating the material for 5 to 8 hours; the mass volume of the oxidized coal nanosheets and the amine-containing compound is 3g:1 to 6mL, and the mass ratio of the oxidized coal nanosheets to the oxidized coal-based graphene quantum dots is 5:1 to 30:1; further preferably, the amine-containing compound is added and then hydroheating the material at 100°C for 6 hours; the mass volume of the oxidized coal nanosheets and the amine-containing compound is 1g:1mL, and the mass ratio of the oxidized coal nanosheets to the oxidized coal-based graphene quantum dots is 20:1.
[0011] The method for preparing a low-dimensional coal-based hard carbon material with both high sodium storage capacity and high initial coulombic efficiency, wherein the graphite plate is any one of ordinary graphite, high-purity graphite, ultra-high purity graphite or highly oriented pyrolytic graphite, and the fixed pressure ranges from 3 to 30 kPa; preferably, the fixed pressure ranges from 3 to 20 kPa; further preferably, the fixed pressure is 20 kPa.
[0012] The method for preparing a low-dimensional coal-based hard carbon material with high sodium storage capacity and high initial coulombic efficiency comprises the following steps: the high-temperature calcination is performed under the protection of a nitrogen atmosphere and the temperature is raised to 800 to 1500°C for 1 to 6 hours; the heating rate is 1 to 10°C min -1 Preferably, the high temperature calcination temperature is 800-1300°C, the holding time is 2-6h, and the heating rate is 5-10°C min -1 ; Further preferably, the temperature is raised to 1300°C during high temperature calcination, and the holding time is 2h; the heating rate is 5°C min -1 .
[0013] The method for preparing the low-dimensional coal-based hard carbon material having both high sodium storage capacity and high initial coulombic efficiency comprises the following steps:
[0014] (1) Liquid phase oxidation of Xinjiang bituminous coal was carried out in a nitric acid / sulfuric acid oxidation system, and oxidized coal nanosheets and oxidized coal-based graphene quantum dots were obtained by centrifugation, dialysis, rotary evaporation and cold drying;
[0015] (2) dissolving a mixture of oxidized coal-based graphene quantum dots and oxidized coal nanosheets or oxidized coal nanosheets in deionized water; the mass volume ratio of the oxidized coal nanosheets to the deionized water is 1 g:100 mL;
[0016] (3) After the two are completely dissolved in water, add the amine-containing compound and stir magnetically for 1 to 8 hours;
[0017] (4) placing the mixed solution into a hydrothermal reactor for hydrothermal reaction to fully cross-link the amine-containing compound with the oxidized coal nanosheets and the oxidized coal-based graphene quantum dots;
[0018] (5) cold-drying the cross-linked mixed solution to obtain a low-dimensional coal-based hard carbon precursor, which is sandwiched between two graphite plates and a fixed pressure is applied to the graphite plates;
[0019] (6) The graphite plate sandwiched with the low-dimensional coal-based hard carbon precursor is placed in a tubular furnace, calcined at high temperature in an inert atmosphere, and cooled to obtain a low-dimensional coal-based hard carbon material with both high sodium storage capacity and high initial coulombic efficiency.
[0020] The method for preparing a low-dimensional coal-based hard carbon material having both high sodium storage capacity and high initial coulombic efficiency is characterized in that the preparation of oxidized coal nanosheets and oxidized coal-based graphene quantum dots:
[0021] (a) ball-milling raw Xinjiang bituminous coal and passing it through a 200-mesh sieve to obtain coal powder;
[0022] (b) Add 30 g of coal powder to a 5 L measuring cylinder, and slowly add 720 mL of a mixture of sulfuric acid and nitric acid under stirring, with the volume ratio of sulfuric acid to nitric acid being 1:1 to 3:1, and react for 3 to 6 hours;
[0023] (c) After the reaction is completed, the mixture is diluted into 3 L of deionized water and centrifuged at 8000-10000 rpm for 5-10 min;
[0024] (d) After discarding the upper acid solution, dissolve the precipitate in the centrifuge tube in 3-5 L of deionized water, sonicate for 1-3 h to completely dissolve it, and then place it in a dialysis bag for dialysis;
[0025] (e) After the solution is dialyzed to neutrality, it is centrifuged again, and large particles that are not completely oxidized are precipitated. The supernatant is concentrated by a rotary evaporator at 60-80° C.;
[0026] (f) Finally, the concentrated solution is freeze-dried to obtain oxidized coal-based graphene quantum dots; the precipitated large particles are collected to obtain oxidized coal nanosheets.
[0027] The low-dimensional coal-based hard carbon material prepared by the above method has both high sodium storage capacity and high initial coulombic efficiency.
[0028] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0029] (1) The present invention extracts the aromatic basic structural units in Xinjiang bituminous coal by liquid phase oxidation and converts them into active components such as oxidized coal nanosheets and oxidized coal-based graphene quantum dots.
[0030] (2) Using amine-containing small molecules as cross-linking agents, the above-mentioned active components are self-assembled by covalent bonding to construct low-dimensional coal-based precursor materials.
[0031] (3) Through graphite crystal template-assisted calcination, the order of pseudo-graphite domains in the coal-based hard carbon microstructure is increased and the defect sites are reduced, thereby preparing a low-dimensional coal-based hard carbon sodium storage material with both high capacity and high initial Coulombic efficiency.
[0032] (4) The low-dimensional coal-based hard carbon material is used as the negative electrode of sodium ion battery at 0.02A g -1 The specific capacity of sodium storage can reach 279.60~420.40mA hg -1 , while also having a high initial Coulomb efficiency of 85.53% to 97.59%.
[0033] (5) This low-dimensional coal-based hard carbon material has low preparation cost, simple process and excellent electrochemical performance, which can provide a technical basis for the commercial preparation of coal-based hard carbon negative electrode materials for sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 (a), (b), and (c) are respectively the appearance of the low-dimensional coal-based precursor prepared in Example 1, the appearance of the low-dimensional coal-based hard carbon, and the appearance of the low-dimensional coal-based hard carbon material at 0.02A g -1 Charge and discharge curves under current density;
[0035] Figure 2 (a), (b), and (c) are respectively the appearance of the low-dimensional coal-based precursor prepared in Example 2, the appearance of the low-dimensional coal-based hard carbon, and the appearance of the low-dimensional coal-based hard carbon material at 0.02A g -1 Charge and discharge curves under current density;
[0036] Figure 3 (a), (b), and (c) are respectively the appearance of the low-dimensional coal-based precursor prepared in Example 3, the appearance of the low-dimensional coal-based hard carbon, and the appearance of the low-dimensional coal-based hard carbon material at 0.02Ag. -1 Charge and discharge curves under current density;
[0037] Figure 4 (a), (b), and (c) are respectively the appearance of the low-dimensional coal-based precursor prepared in Example 4, the appearance of the low-dimensional coal-based hard carbon, and the appearance of the low-dimensional coal-based hard carbon material at 0.02Ag. -1 Charge and discharge curves under current density;
[0038] Figure 5 (a), (b), and (c) are respectively the appearance of the low-dimensional coal-based precursor prepared in Example 5, the appearance of the low-dimensional coal-based hard carbon, and the appearance of the low-dimensional coal-based hard carbon material at 0.02Ag.-1 Charge and discharge curves under current density;
[0039] Figure 6 (a), (b), and (c) are respectively the appearance of the low-dimensional coal-based precursor prepared in Example 6, the appearance of the low-dimensional coal-based hard carbon, and the appearance of the low-dimensional coal-based hard carbon material at 0.02Ag. -1 Charge and discharge curves under current density;
[0040] Figure 7 (a), (b), and (c) are respectively the appearance of the low-dimensional coal-based precursor prepared in Example 7, the appearance of the low-dimensional coal-based hard carbon, and the appearance of the low-dimensional coal-based hard carbon material at 0.02Ag -1 Charge and discharge curves under current density. DETAILED DESCRIPTION
[0041] The present invention is further illustrated below in conjunction with specific examples. The examples are implemented based on the technical solutions of the present invention. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0042] The preparation of oxidized coal nanosheets and oxidized coal-based graphene quantum dots comprises the following steps:
[0043] (a) ball-milling raw Xinjiang bituminous coal and passing it through a 200-mesh sieve to obtain coal powder;
[0044] (b) Add 30 g of coal powder into a 5 L measuring cylinder, and slowly add 720 mL of a mixture of sulfuric acid and nitric acid (the volume ratio of sulfuric acid to nitric acid is 3:1, and the reaction is carried out for 5 h) under a stirrer;
[0045] (c) After the reaction, the mixture was diluted into 3 L of deionized water and centrifuged at 9000 rpm for 8 min;
[0046] (d) After discarding the upper acid solution, the precipitate in the centrifuge tube was dissolved in 5 L of deionized water, sonicated for 3 h to completely dissolve it, and then placed in a dialysis bag for dialysis;
[0047] (e) After the solution is dialyzed to neutrality, it is centrifuged again, and large particles that are not completely oxidized are precipitated. The supernatant is concentrated using a rotary evaporator at 75° C.
[0048] (f) Finally, the concentrated solution is freeze-dried to obtain oxidized coal-based graphene quantum dots; the precipitated large particles are collected to obtain oxidized coal nanosheets.
[0049] The oxidized coal nanosheets and oxidized coal-based graphene quantum dots prepared above are used in the preparation of low-dimensional coal-based hard carbon materials having both high sodium storage capacity and high initial coulombic efficiency in the following Examples 1-7.
[0050] Example 1
[0051] A method for synthesizing a low-dimensional coal-based hard carbon material with high sodium storage capacity and high initial coulombic efficiency, wherein the precursor of the material is prepared by cross-linking and deoxidation reduction of oxidized coal nanosheets and urea; the method specifically comprises the following steps:
[0052] 0.30 g of oxidized coal nanosheets were dissolved in 30 mL of deionized water. After the nanosheets were completely dissolved, 100 μL of urea solution was added and stirred on a magnetic stirrer for 1 h. The mixed solution was then poured into a 50 mL hydrothermal kettle and kept at 100 ° C for 8 h to fully cross-link the oxidized coal nanosheets with urea. Finally, the cross-linked liquid was lyophilized to obtain a precursor.
[0053] The cold-dried precursor was sandwiched between two ordinary graphite plates, and an electric isostatic press was used to apply 3 kPa pressure to the graphite plates to ensure that the precursor could be in uniform contact with the graphite plates. Then the graphite plates were loaded into a porcelain boat and placed in a tube furnace. Nitrogen was pre-flowed for 0.5 h at room temperature to remove the air in the tube. The temperature was set at 5 °C min-1 under a nitrogen atmosphere. -1 The temperature is raised to 1000°C at a rate of , kept at that temperature for 3 hours, and then the sample is taken out after being cooled to room temperature, which is a low-dimensional coal-based hard carbon material.
[0054] The low-dimensional coal-based hard carbon material prepared above is used as the negative electrode of the sodium ion battery to assemble the sodium ion battery.
[0055] The prepared sodium ion battery negative material powder, Ketjen black, and sodium carboxymethyl cellulose were mixed and ground in a mass ratio of 8:1:1. After being fully ground into fine powder, an appropriate amount of deionized water was added and further ground into a slurry with suitable viscosity. The slurry was evenly applied on the copper foil with a coater, dried in the shade, and vacuum dried at 110°C for 10 hours. It was cut into circular negative electrode sheets with a diameter of 10 mm with a cutting machine for use. The half-cell was assembled in an argon-filled glove box, with sodium metal as the counter electrode and 1 mol NaPF6 dissolved in dimethyl carbonate as the electrolyte. Assembled into a CR2025 button cell, and electrochemical charge and discharge tests were performed after standing for 6 hours. The test voltage range was 0.01V-3V, and the current density was 0.02Ag. -1 Test results see Figure 1 , the reversible specific capacity is 279.60 mAh g -1 , the first coulombic efficiency is 85.53%, which has good electrochemical sodium storage performance.
[0056] Example 2
[0057] A method for synthesizing a low-dimensional coal-based hard carbon material with high sodium storage capacity and high initial coulombic efficiency, wherein the material is prepared by cross-linking and deoxidizing oxidized coal nanosheets and oxidized coal-based graphene quantum dots with triethylenetetramine; the method specifically comprises the following steps:
[0058] Oxidized coal nanosheets and oxidized coal-based graphene quantum dots (0.30 g of oxidized coal nanosheets, the mass ratio of oxidized coal nanosheets to oxidized coal-based graphene quantum dots is 5:1) are dissolved in 30 mL of deionized water, and after they are completely dissolved, 200 μL of triethylenetetramine solution is added and stirred on a magnetic stirrer for 2 h, and then the mixed solution is poured into a 50 mL hydrothermal autoclave and kept warm at 110 ° C for 6 h, so that the oxidized coal nanosheets and oxidized coal-based graphene quantum dots can be fully cross-linked with the triethylenetetramine solution, and finally the cross-linked liquid is cold-dried to obtain a precursor;
[0059] The cold-dried precursor was sandwiched between two high-purity graphite plates, and an electric isostatic press was used to apply 6 kPa pressure to the graphite plates to ensure that the precursor could be in uniform contact with the graphite plates. Then the graphite plates were loaded into a porcelain boat and placed in a tubular furnace. Nitrogen was pre-flowed for 0.5 h at room temperature to remove the air in the tube. The temperature was set at 10 °C min-1 under a nitrogen atmosphere. -1 The temperature is raised to 800°C at a rate of , kept at that temperature for 3 hours, and then the sample is taken out after being cooled to room temperature, which is a low-dimensional coal-based hard carbon material.
[0060] The low-dimensional coal-based hard carbon material prepared above is used as the negative electrode of the sodium ion battery to assemble the sodium ion battery.
[0061] The prepared sodium ion battery negative material powder, Ketjen black, and sodium carboxymethyl cellulose were mixed and ground in a mass ratio of 8:1:1. After being fully ground into fine powder, an appropriate amount of deionized water was added and further ground into a slurry with suitable viscosity. The slurry was evenly applied on the copper foil with a coater, dried in the shade, and vacuum dried at 110°C for 10 hours. It was cut into circular negative electrode sheets with a diameter of 10 mm with a cutting machine for use. The half-cell was assembled in an argon-filled glove box, with sodium metal as the counter electrode and 1 mol NaPF6 dissolved in dimethyl carbonate as the electrolyte. Assembled into a CR2025 button cell, and electrochemical charge and discharge tests were performed after standing for 8 hours. The test voltage range was 0.01V-3V, and the current density was 0.02Ag. -1 , test results see Figure 2 , the reversible specific capacity is 313.50 mAh g -1 , the first coulombic efficiency is 90.37%, which has good electrochemical sodium storage performance.
[0062] Example 3
[0063] A method for synthesizing a low-dimensional coal-based hard carbon material with high sodium storage capacity and high initial coulombic efficiency, wherein the material is prepared by cross-linking and deoxidizing and reducing oxidized coal nanosheets and oxidized coal-based graphene quantum dots with p-phenylenediamine; the method specifically comprises the following steps:
[0064] Oxidized coal nanosheets and oxidized coal-based graphene quantum dots (0.30 g of oxidized coal nanosheets, the mass ratio of oxidized coal nanosheets to oxidized coal-based graphene quantum dots is 10:1) are dissolved in 30 mL of deionized water, and after they are completely dissolved, 500 μL of p-phenylenediamine solution is added and stirred on a magnetic stirrer for 1 hour, and then the mixed solution is poured into a 50 mL hydrothermal autoclave and kept warm at 80°C for 8 hours to allow the oxidized coal and oxidized coal-based graphene quantum dots to be fully cross-linked with p-phenylenediamine. Finally, the cross-linked liquid is cold-dried to obtain a precursor.
[0065] The cold-dried precursor was sandwiched between two highly oriented pyrolytic graphite plates, and an electric isostatic press was used to apply a pressure of 10 kPa to the graphite plates to ensure that the precursor could be in uniform contact with the graphite plates. Then the graphite plates were loaded into a porcelain boat and placed in a tubular furnace. Nitrogen was pre-flowed for 0.5 h at room temperature to remove the air in the tube. The temperature was set at 10 °C min-1 under a nitrogen atmosphere. -1 The temperature is raised to 1000°C at a rate of , kept at that temperature for 6 hours, and then the sample is taken out after being cooled to room temperature, which is a low-dimensional coal-based hard carbon material.
[0066] The low-dimensional coal-based hard carbon material prepared above is used as the negative electrode of the sodium ion battery to assemble the sodium ion battery.
[0067] The prepared sodium ion battery negative material powder, Ketjen black, and sodium carboxymethyl cellulose were mixed and ground in a mass ratio of 8:1:1. After being fully ground into fine powder, an appropriate amount of deionized water was added and further ground into a slurry with suitable viscosity. The slurry was evenly applied on the copper foil with a coater, dried in the shade, and vacuum dried at 110°C for 10 hours. It was cut into circular negative electrode sheets with a diameter of 10 mm with a cutting machine for use. The half-cell was assembled in an argon-filled glove box, with sodium metal as the counter electrode and 1 mol NaPF6 dissolved in dimethyl carbonate as the electrolyte. Assembled into a CR2025 button cell, and electrochemical charge and discharge tests were performed after standing for 8 hours. The test voltage range was 0.01V-3V, and the current density was 0.02Ag. -1 , test results see Figure 3 , the reversible specific capacity is 342.5 mAh g -1 , the first coulombic efficiency is 87.18%, which has good electrochemical sodium storage performance.
[0068] Example 4
[0069] A method for synthesizing a low-dimensional coal-based hard carbon material with high sodium storage capacity and high initial coulombic efficiency, wherein the material is prepared by cross-linking and deoxidizing octanediamine with oxidized coal nanosheets and oxidized coal-based graphene quantum dots; the method specifically comprises the following steps:
[0070] The oxidized coal nanosheets and oxidized coal-based graphene quantum dots (0.30 g of oxidized coal nanosheets, the mass ratio of oxidized coal nanosheets to oxidized coal-based graphene quantum dots is 30:1) are dissolved in 30 mL of deionized water, and after they are completely dissolved, 600 μL of octanediamine solution is added and stirred on a magnetic stirrer for 3 h, and then the mixed solution is poured into a 50 mL hydrothermal autoclave and kept warm at 120 ° C for 7 h to allow the oxidized coal nanosheets and oxidized coal-based graphene quantum dots to be fully cross-linked with octanediamine. Finally, the cross-linked liquid is cold-dried to obtain a precursor.
[0071] The cold-dried precursor was sandwiched between two ultra-high purity graphite plates, and an electric isostatic press was used to apply 10 kPa pressure to the graphite plates to ensure that the precursor could be in uniform contact with the graphite plates. Then the graphite plates were loaded into a porcelain boat and placed in a tube furnace. Nitrogen was pre-flowed for 0.5 h at room temperature to remove the air in the tube. The temperature was set at 5 °C min-1 under a nitrogen atmosphere. -1 The temperature is raised to 1300°C at a rate of , kept at that temperature for 3 hours, and the sample is taken out after being cooled to room temperature, which is a low-dimensional coal-based hard carbon material.
[0072] The low-dimensional coal-based hard carbon material prepared above is used as the negative electrode of the sodium ion battery to assemble the sodium ion battery.
[0073] The prepared sodium ion battery negative material powder, Ketjen black, and sodium carboxymethyl cellulose were mixed and ground in a mass ratio of 8:1:1. After being fully ground into fine powder, an appropriate amount of deionized water was added and further ground into a slurry with suitable viscosity. The slurry was evenly applied on the copper foil with a coater, dried in the shade, and vacuum dried at 110°C for 10 hours. It was cut into circular negative electrode sheets with a diameter of 10 mm with a cutting machine for use. The half-cell was assembled in an argon-filled glove box, with sodium metal as the counter electrode and 1 mol NaPF6 dissolved in dimethyl carbonate as the electrolyte. Assembled into a CR2025 button cell, and electrochemical charge and discharge tests were performed after standing for 8 hours. The test voltage range was 0.01V-3V, and the current density was 0.02Ag. -1 , test results see Figure 4 , the reversible specific capacity is 371.24 mAh g -1 , the first coulombic efficiency is 92.26%, which has good electrochemical sodium storage performance.
[0074] Example 5
[0075] A method for synthesizing a low-dimensional coal-based hard carbon material with high sodium storage capacity and high initial coulombic efficiency, wherein the material is prepared by cross-linking and deoxidizing oxidized coal nanosheets and oxidized coal-based graphene quantum dots with ethylenediamine; the method specifically comprises the following steps:
[0076] Oxidized coal nanosheets and oxidized coal-based graphene quantum dots (0.30 g of oxidized coal nanosheets, the mass ratio of oxidized coal nanosheets to oxidized coal-based graphene quantum dots is 30:1) are dissolved in 30 mL of deionized water, and after they are completely dissolved, 300 μL of ethylenediamine solution is added and stirred on a magnetic stirrer for 1 hour, and then the mixed solution is poured into a 50 mL hydrothermal autoclave and kept warm at 100 ° C for 5 hours to allow the oxidized coal nanosheets and oxidized coal-based graphene quantum dots to be fully cross-linked with ethylenediamine. Finally, the cross-linked liquid is cold-dried to obtain a precursor.
[0077] The cold-dried precursor was sandwiched between two ultra-high purity graphite plates, and an electric isostatic press was used to apply a pressure of 20 kPa to the graphite plates to ensure that the precursor could be in uniform contact with the graphite plates. Then the graphite plates were loaded into a porcelain boat and placed in a tubular furnace. Nitrogen was pre-flowed for 0.5 h at room temperature to remove the air in the tube. The temperature was set at 5 °C min-1 under a nitrogen atmosphere. -1 The temperature is raised to 1300°C at a rate of , kept at this temperature for 2 hours, and the sample is taken out after being cooled to room temperature, which is a low-dimensional coal-based hard carbon material.
[0078] The low-dimensional coal-based hard carbon material prepared above is used as the negative electrode of the sodium ion battery to assemble the sodium ion battery.
[0079] The prepared sodium ion battery negative material powder, Ketjen black, and sodium carboxymethyl cellulose were mixed and ground in a mass ratio of 8:1:1. After being fully ground into fine powder, an appropriate amount of deionized water was added and further ground into a slurry with suitable viscosity. The slurry was evenly applied on the copper foil with a coater, dried in the shade, and vacuum dried at 110°C for 10 hours. It was cut into circular negative electrode sheets with a diameter of 10 mm with a cutting machine for use. The half-cell was assembled in an argon-filled glove box, with sodium metal as the counter electrode and 1 mol NaPF6 dissolved in dimethyl carbonate as the electrolyte. Assembled into a CR2025 button cell, and electrochemical charge and discharge tests were performed after standing for 8 hours. The test voltage range was 0.01V-3V, and the current density was 0.02Ag. -1 , test results see Figure 5 , the reversible specific capacity is 348.4 mAh g -1 , the first coulombic efficiency is 89.84%, which has good electrochemical sodium storage performance.
[0080] Example 6
[0081] A method for synthesizing a low-dimensional coal-based hard carbon material with high sodium storage capacity and high initial coulombic efficiency, wherein the material is prepared by cross-linking and deoxidation reduction of oxidized coal nanosheets and oxidized coal-based graphene quantum dots with polyetheramine; the method specifically comprises the following steps:
[0082] Oxidized coal nanosheets and oxidized coal-based graphene quantum dots (0.30 g of oxidized coal nanosheets, the mass ratio of oxidized coal nanosheets to oxidized coal-based graphene quantum dots is 20:1) are dissolved in 30 mL of deionized water, and after they are completely dissolved, 300 μL of polyetheramine solution is added and stirred on a magnetic stirrer for 1 hour, and then the mixed solution is poured into a 50 mL hydrothermal autoclave and kept warm at 100 ° C for 6 hours to allow the oxidized coal nanosheets and oxidized coal-based graphene quantum dots to be fully cross-linked with the polyetheramine. Finally, the cross-linked liquid is cold-dried to obtain a precursor.
[0083] The cold-dried precursor was sandwiched between two ultra-high purity graphite plates, and an electric isostatic press was used to apply a pressure of 20 kPa to the graphite plates to ensure that the precursor could be in uniform contact with the graphite plates. Then the graphite plates were loaded into a porcelain boat and placed in a tubular furnace. Nitrogen was pre-flowed for 0.5 h at room temperature to remove the air in the tube. The temperature was set at 5 °C min-1 under a nitrogen atmosphere. -1 The temperature is raised to 1300°C at a rate of , kept at that temperature for 2 hours, and the sample is taken out after being cooled to room temperature, which is a low-dimensional coal-based hard carbon material.
[0084] The low-dimensional coal-based hard carbon material prepared above is used as the negative electrode of the sodium ion battery to assemble the sodium ion battery.
[0085] The prepared sodium ion battery negative material powder, Ketjen black, and sodium carboxymethyl cellulose were mixed and ground in a mass ratio of 8:1:1. After being fully ground into fine powder, an appropriate amount of deionized water was added and further ground into a slurry with suitable viscosity. The slurry was evenly applied on the copper foil with a coater, dried in the shade, and vacuum dried at 110°C for 10 hours. It was cut into circular negative electrode sheets with a diameter of 10 mm with a cutting machine for use. The half-cell was assembled in an argon-filled glove box, with sodium metal as the counter electrode and 1 mol NaPF6 dissolved in dimethyl carbonate as the electrolyte. Assembled into a CR2025 button cell, and electrochemical charge and discharge tests were performed after standing for 8 hours. The test voltage range was 0.01V-3V, and the current density was 0.02Ag. -1 , test results see Figure 6 , the reversible specific capacity is 420.40 mAh g -1 , the first coulombic efficiency is 91.97%, which has good electrochemical sodium storage performance.
[0086] Example 7
[0087] A method for synthesizing a low-dimensional coal-based hard carbon material with high sodium storage capacity and high initial coulombic efficiency, wherein the material is prepared by cross-linking and deoxidizing oxidized coal nanosheets and oxidized coal-based graphene quantum dots with polyimide; the method specifically comprises the following steps:
[0088] Oxidized coal nanosheets and oxidized coal-based graphene quantum dots (0.30 g of oxidized coal nanosheets, the mass ratio of oxidized coal nanosheets to oxidized coal-based graphene quantum dots is 30:1) are dissolved in 30 mL of deionized water, and after they are completely dissolved, 400 μL of polyimide solution is added and stirred on a magnetic stirrer for 1 h, and then the mixed solution is poured into a 50 mL hydrothermal autoclave and kept warm at 100 ° C for 6 h, so that the oxidized coal nanosheets and oxidized coal-based graphene quantum dots can be fully cross-linked with the polyimide. Finally, the cross-linked liquid is cold-dried to obtain a precursor.
[0089] The cold-dried precursor was sandwiched between two ultra-high purity graphite plates, and an electric isostatic press was used to apply a pressure of 20 kPa to the graphite plates to ensure that the precursor could be in uniform contact with the graphite plates. Then the graphite plates were loaded into a porcelain boat and placed in a tubular furnace. Nitrogen was pre-flowed for 0.5 h at room temperature to remove the air in the tube. The temperature was set at 5 °C min-1 under a nitrogen atmosphere. -1 The temperature is raised to 1300°C at a rate of , kept at this temperature for 2 hours, and the sample is taken out after being cooled to room temperature, which is a low-dimensional coal-based hard carbon material.
[0090] The low-dimensional coal-based hard carbon material prepared above is used as the negative electrode of the sodium ion battery to assemble the sodium ion battery.
[0091] The prepared sodium ion battery negative material powder, Ketjen black, and sodium carboxymethyl cellulose were mixed and ground in a mass ratio of 8:1:1. After being fully ground into fine powder, an appropriate amount of deionized water was added and further ground into a slurry with suitable viscosity. The slurry was evenly applied on the copper foil with a coater, dried in the shade, and vacuum dried at 110°C for 10 hours. It was cut into circular negative electrode sheets with a diameter of 10 mm with a cutting machine for use. The half-cell was assembled in an argon-filled glove box, with sodium metal as the counter electrode and 1 mol NaPF6 dissolved in dimethyl carbonate as the electrolyte. Assembled into a CR2025 button cell, and electrochemical charge and discharge tests were performed after standing for 8 hours. The test voltage range was 0.01V-3V, and the current density was 0.02Ag. -1 , test results see Figure 7 , the reversible specific capacity is 329.05 mAh g -1 , the first coulombic efficiency is 97.59%, which has good electrochemical sodium storage performance.
[0092] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a low-dimensional coal-based hard carbon material having both high sodium storage capacity and high initial coulombic efficiency, characterized in that: Xinjiang bituminous coal is oxidized and depolymerized by liquid phase oxidation method to obtain oxidized coal nanosheets and oxidized coal-based graphene quantum dots; the mixture of oxidized coal nanosheets and oxidized coal-based graphene quantum dots or oxidized coal nanosheets are cross-linked, self-assembled and deoxidized and reduced by amine compounds to obtain low-dimensional coal-based precursors; the coal-based precursors are calcined with the assistance of graphite plates, and then low-dimensional coal-based hard carbon materials are prepared by high-temperature calcination.
2. The method for preparing a low-dimensional coal-based hard carbon material having both high sodium storage capacity and high initial coulombic efficiency according to claim 1, characterized in that: The Xinjiang bituminous coal was oxidatively depolymerized for 3 to 6 hours using a nitric acid / sulfuric acid oxidation system. The mass volume ratio of coal powder to the oxidation system was 1 g:24 mL; the volume ratio of sulfuric acid to nitric acid was 1:1 to 3:
1.
3. The method for preparing a low-dimensional coal-based hard carbon material having both high sodium storage capacity and high initial coulombic efficiency according to claim 1, characterized in that: The amine-containing compound is any one of ethylenediamine, octanediamine, o- / m- / p-phenylenediamine, diethylenetriamine, triethylenetetramine, polyetheramine, polyimide, piperazine or urea.
4. The method for preparing a low-dimensional coal-based hard carbon material having both high sodium storage capacity and high initial coulombic efficiency according to claim 1, characterized in that: After adding the amine-containing compound, hydroheating is performed at 80-120° C. for 4-8 hours; the mass volume of the oxidized coal nanosheets and the amine-containing compound is 3g:1-8mL, and the mass ratio of the oxidized coal nanosheets to the oxidized coal-based graphene quantum dots is 3:1-100:
1.
5. The method for preparing a low-dimensional coal-based hard carbon material having both high sodium storage capacity and high initial coulombic efficiency according to claim 1, characterized in that: The graphite plate is any one of common graphite, high-purity graphite, ultra-high-purity graphite or highly oriented pyrolytic graphite, and the fixing pressure ranges from 3 to 30 kPa.
6. The method for preparing a low-dimensional coal-based hard carbon material having both high sodium storage capacity and high initial coulombic efficiency according to claim 1, characterized in that: The high temperature calcination is to heat the material to 800-1500°C under the protection of nitrogen atmosphere, and the holding time is 1-6h; the heating rate is 1-10°C min -1 .
7. The method for preparing a low-dimensional coal-based hard carbon material having both high sodium storage capacity and high initial coulombic efficiency according to claim 1, characterized in that: The following steps are involved: (1) Liquid phase oxidation of Xinjiang bituminous coal was carried out in a nitric acid / sulfuric acid oxidation system, and oxidized coal nanosheets and oxidized coal-based graphene quantum dots were obtained by centrifugation, dialysis, rotary evaporation and cold drying; (2) dissolving a mixture of oxidized coal-based graphene quantum dots and oxidized coal nanosheets or oxidized coal nanosheets in deionized water; the mass volume ratio of the oxidized coal nanosheets to the deionized water is 1 g:100 mL; (3) After the two are completely dissolved in water, add the amine-containing compound and stir magnetically for 1 to 8 hours; (4) placing the mixed solution into a hydrothermal reactor for hydrothermal reaction to fully cross-link the amine-containing compound with the oxidized coal nanosheets and the oxidized coal-based graphene quantum dots; (5) cold-drying the cross-linked mixed solution to obtain a low-dimensional coal-based hard carbon precursor, which is sandwiched between two graphite plates and a fixed pressure is applied to the graphite plates; (6) The graphite plate sandwiched with the low-dimensional coal-based hard carbon precursor is placed in a tubular furnace, calcined at high temperature in an inert atmosphere, and cooled to obtain a low-dimensional coal-based hard carbon material with both high sodium storage capacity and high initial coulombic efficiency.
8. The method for preparing a low-dimensional coal-based hard carbon material having both high sodium storage capacity and high initial coulombic efficiency according to claim 1 or 7, characterized in that: Preparation of oxidized coal nanosheets and oxidized coal-based graphene quantum dots: (a) ball-milling raw Xinjiang bituminous coal and passing it through a 200-mesh sieve to obtain coal powder; (b) Add 30 g of coal powder into a container, slowly add 720 mL of a mixture of sulfuric acid and nitric acid under stirring, and react for 3 to 6 hours; (c) After the reaction is completed, the mixture is diluted into 3 L of deionized water and centrifuged at 8000-10000 rpm for 5-10 min; (d) After discarding the upper acid solution, dissolve the precipitate in the centrifuge tube in 3-5 L of deionized water, sonicate for 1-3 h to completely dissolve it, and then place it in a dialysis bag for dialysis; (e) After the solution is dialyzed to neutrality, it is centrifuged again, and large particles that are not completely oxidized are precipitated. The supernatant is concentrated by a rotary evaporator at 60-80° C.; (f) Finally, the concentrated solution is freeze-dried to obtain oxidized coal-based graphene quantum dots; the precipitated large particles are collected to obtain oxidized coal nanosheets.
9. A low-dimensional coal-based hard carbon material having high sodium storage capacity and high initial coulombic efficiency prepared by the method of any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of modified hard carbon negative electrode material with high first coulombic efficiency and related sodium ion battery
CN114709418A
Battery negative electrode coal-based hard carbon material as well as preparation method and application thereof
CN116190646A
Coal-based hard carbon negative electrode material, integrated preparation method thereof and sodium ion battery
CN118164470A
Heteroatom-doped porous hard carbon negative electrode material and preparation method and application thereof
CN118289737A
Composite coal-based hard carbon as well as preparation method and application thereof
CN119018877A
Cited By
Sodium-ion battery hard carbon negative electrode material and preparation method and application thereof
CN120964770A
